Corporate debt maturity structure: the role of firm level and institutional determinants in selected African countries - Etudaiye-Muhtar, Oyebola Fatima; Ahmad, Rubi; Tunde, Matemilola Bolaji (Routledge, 2017)
An appropriate debt maturity structure is essential for firms to enable them align asset structure to liabilities to prevent a mismatch. This study investigates the role of firm-level and institutional variables on debt maturity structure in selected African countries. Using panel generalised method of moment that addresses endogeneity problem; our findings reveal a dynamic process of adjustment to optimal debt maturity structure. Furthermore, firm-level variables (leverage, asset structure and firm size) provide support for the contracting cost, signalling and matching principle theories of debt maturity structure. Results of institutional variables suggest that better developed institutions promote long-term debt maturity structures.